COMPETENCE BASED EDUCATION AND TRAINING AND EMPLOYABILITY OF VISUALLY IMPAIRED LEARNERS IN TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING INSTITUTIONS IN KENYA - MUTUA, PRISCILLAH N. (My University, 2019)
Curriculum is the vehicle through which a nation empowers her people with the essential knowledge and skills, attitudes and values that allow them to be empowered for individual and general development. Therefore, the curriculum ought to meet the needs of an individual and also for the nation. This study explore competence-based education and training and employability of visually impaired learners in TVET institutions in Kenya; establish the influence of adaptability of facilities applied in CBET implementation on the acquisition of employable skills among visually impaired learners in TVET institutions in Kenya; examine the extent to which trainers’ qualifications in CBET influence the acquisition of employable skills among visually impaired learners in TVET institutions in Kenya and establish the effect of competence based education and training on employability rates of the visually impaired graduates from TVET institutions in Kenya. The study was founded on job skilling theory by Dreyfus and Dreyfus and was complemented by apprenticeship skills formation theory by Brandt, Farmer, and Buckmaster as well as the ladder participation theory by Engestrom. The study applied a mixed methods research design. It targeted 2 principals, 20 Heads Of Departments (HODs), 70 trainers, 150 visually impaired learners and graduates of Machakos Technical Institute for the Blind and Sikri Technical Training Institute for Deaf-Blind, 2 Ministry of Education officials in charge of Technical Vocational and Education Training (TVET) - Curriculum Development Accreditation and Certification Council (CDACC) officials, 10 Ministry Of Labour (MOL) officials, 10 members of civil society groups and 5 managers of industries giving a total of 269 respondents. The sample size was thus 49%. A census of the trainers was taken while purposive technique was used to sample the principals MOL officials, HODs, MOE officials, civil society groups and industry managers. Snowball technique was also used to select visually impaired graduates. Primary data was collected using questionnaires, interview schedules, and focused group discussion guide, visual images as well as observation schedules. Pilot study was conducted in Kerugoya Vocational Training for the Blind to test validity and reliability of the instruments. Qualitative data was analysed using content analysis majorly thematic analysis while quantitative data was analysed using descriptive and inferential analyses where Pearson correlation analysis was used to determine significant associations on the variables. Bivariate and multiple regression analyses were used in generating regression coefficients, t statistics and associated p values that guided the testing of the hypotheses. All tests were done at 0.05 level of significance. The study found that applicability of CBET curriculum (β = 0.534, t = 7.294, p = .000), adaptability of facilities used in CBET implementation (β = 0.709, t = 9.459, p = .000) and trainers’ qualifications in CBET (β = 0.881, t = 8.797, p=.000) positively and significantly influenced the acquisition of employable skills among the visually impaired learners in TVET institutions in Kenya. The study also found that CBET positively and significantly influenced the employability rates of visually impaired graduates from TVET institutions in Kenya. The study further established that industry linkage and occupational standards had a significant moderating effect on the relationship between CBET and acquisition of employable skills among the visually impaired learners in these institutions. The study therefore concluded that the level of acquisition of employable skills among the visually impaired learners in TVET institutions was considerably affected by the level of applicability of the CBET curriculum. The study also concluded that the adaptability of facilities used in CBET implementation and trainers’ qualifications in CBET were key determinants of the acquisition of employable skills among these learners. Recommendations to MOE, MOL, TVET institutions, civil society groups, industries and VI graduates were made. Suggestions for further study were given.
Keywords: Curriculum